2020
DOI: 10.1093/mnras/staa1349
|View full text |Cite
|
Sign up to set email alerts
|

Accretion disc–jet couplings in X-ray binaries

Abstract: When the matter from a companion star is accreted towards the central compact accretor, i.e. a black hole (BH) or a neutron star (NS), an accretion disc and a jet outflow will form, providing bight X-ray and radio emission, which is known as X-ray binaries (XRBs). In the low/hard state, there exist disc–jet couplings in XRBs, but it remains uncertain whether the jet power comes from the disc or the central accretor. Moreover, black hole X-ray binaries (BHXRBs) have different properties compared with neutron st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…It is generally believed that the standard track in BHXBs is caused by the hot accretion flow (e.g., [10,12,60]). As shown in Section 3, the typical 'outliers' track is possibly caused by the BZ-jet at approximately the MAD state.…”
Section: Mad In Bhxbsmentioning
confidence: 99%
“…It is generally believed that the standard track in BHXBs is caused by the hot accretion flow (e.g., [10,12,60]). As shown in Section 3, the typical 'outliers' track is possibly caused by the BZ-jet at approximately the MAD state.…”
Section: Mad In Bhxbsmentioning
confidence: 99%
“…In order to account for outflows in the analytical model, Blandford & Begelman (1999) assumed that the accretion rate has a power-law dependence on radius. Based on this assumption, many works have been carried out to study the structure and cooling mechanisms of the accretion disk with outflows (e.g., Gu 2015;Ghoreyshi & Shadmehri 2020;Shen & Gu 2020;Wu et al 2022). Recently, 2D analytical models revealed that the mass accretion rate indeed follows a power-law form (Xie & Yuan 2008;Dotan & Shaviv 2011;Gu 2012;Cao & Gu 2015;Kumar & Gu 2018;Feng et al 2019;Mosallanezhad et al 2021;Zeraatgari et al 2021).…”
Section: Introductionmentioning
confidence: 99%